Producing shared understanding for digital and social innovation: bridging divides with transdisciplinary information experience concepts and methods - Miller, Faye (Palgrave Macmillan, 2020)
Provides a guide to the development of innovative mindsets for new and seasoned researchers, students and other practitioners who collaborate with social science researchers Rather than focusing on how and why specific research methodologies are employed, the book increases meaningful research by developing transferable mindsets, across every stage of the research production Uniquely accessible by conveying key concepts via a combination of theoretical research, allegories and conversations emerging from the author’s unique perspective as a millennial academic researcher of lived experience and documentary filmmaker
Keywords: Réservé UdeM